2009
DOI: 10.1177/0145482x0910300605
|View full text |Cite
|
Sign up to set email alerts
|

A Three-phase Qualitative Study of Dual-Certified Vision Education Professionals in the Southwestern United States

Abstract: The purpose of this qualitative study was to develop a comprehensive understanding of the roles and responsibilities of vision education professionals who are dual-certified as teachers of students with visual impairments and orientation and mobility specialists. Through three phases, the study combined interviews and observations of the vision professionals with interviews with their administrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This finding contradicted what the dual-certified professionals had reported in our study (Griffin-Shirley et al, in press), in which the division was reported as a more even split between the two roles. However, previous studies (see, for example, Griffin-Shirley et al, 2009) suggested this ratio between vision services and O&M services, so the finding that 75% of the parents reported satisfaction with the amount of time and the division of roles that the dual-certified professionals were spending with their children did not come as a surprise.…”
Section: Parents' Satisfaction With Their Children's Current Vision Servicesmentioning
confidence: 87%
See 2 more Smart Citations
“…This finding contradicted what the dual-certified professionals had reported in our study (Griffin-Shirley et al, in press), in which the division was reported as a more even split between the two roles. However, previous studies (see, for example, Griffin-Shirley et al, 2009) suggested this ratio between vision services and O&M services, so the finding that 75% of the parents reported satisfaction with the amount of time and the division of roles that the dual-certified professionals were spending with their children did not come as a surprise.…”
Section: Parents' Satisfaction With Their Children's Current Vision Servicesmentioning
confidence: 87%
“…This could be a central question for future studies as researchers continue to examine what works and what does not work in the current service delivery model of vision education. Part of this ongoing research may involve observing dual-certified professionals nationwide in much the same way as was done with the previous regional model (Griffin-Shirley et al, 2009). The final line of research will involve including students in the examination of the dual-certified vision professional service delivery model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Griffin-Shirley, Pogrund, Smith, and Duemer (2009) Abstract:Organizational environments are environments where conflicts of interest are intense due to business and human interactions. Various problems are experienced in these environments due to both business and human interaction and interpersonal relations.…”
Section: The Use Of Public Transportation and Attitudesmentioning
confidence: 99%